A late Neanderthal tooth from northeastern Italy. Issue 147 (October 2020) - Romandini, Matteo; Oxilia, Gregorio; Bortolini, Eugenio; Peyrégne, Stéphane; Delpiano, Davide; Nava, Alessia; Panetta, Daniele; Di Domenico, Giovanni; Martini, Petra; Arrighi, Simona; Badino, Federica; Figus, Carla; et al.
Abstract: The site of Riparo Broion (Vicenza, northeastern Italy) preserves a stratigraphic sequence documenting the Middle-to-Upper Paleolithic transition, in particular the final Mousterian and the Uluzzian cultures. In 2018, a human tooth was retrieved from a late Mousterian level, representing the first human remain ever found from this rock shelter (Riparo Broion 1). Here, we provide the morphological description and taxonomic assessment of Riparo Broion 1 with the support of classic and virtual morphology, 2D and 3D analysis of the topography of enamel thickness, and DNA analysis. The tooth is an exfoliated right upper deciduous canine, and its general morphology and enamel thickness distribution support attribution to a Neanderthal child. Correspondingly, the mitochondrial DNA sequence from Riparo Broion 1 falls within the known genetic variation of Late Pleistocene Neanderthals, in accordance with newly obtained radiocarbon dates that point to approximately 48 ka cal BP as the most likely minimum age for this specimen. The present work describes novel and direct evidence of the late Neanderthal occupation in northern Italy that preceded the marked cultural and technological shift documented by the Uluzzian layers in the archaeological sequence at Riparo Broion. Here, we provide a new full morphological, morphometric, and taxonomic analysis of Riparo Broion 1, in addition to generating the wider reference sample of Neanderthal and modern human upper deciduous canines. This research contributes to increasing the sample of fossil remains from Italy, as well as the number of currently available upper deciduous canines, which are presently poorly documented in the scientific literature.